TANTANGAN PSIKOLOGIS SANTRI DALAM MENJAGA KONSISTENSI HAFALAN AL-QUR’AN DI PONDOK PESANTREN RAUDHATUL QUR'AN TARAKAN - Wijaya, Fahri; Maulidin, Syarif; Andrianto, Dedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the psychological challenges faced by students in maintaining the consistency of Qur’an memorization at Raudhatul Qur’an Islamic Boarding School, Tarakan. Memorizing the Qur’an is not only a cognitive activity but also a spiritual and psychological process that requires emotional stability and strong self-motivation. However, many students experience psychological pressures such as academic burnout, anxiety during memorization submission sessions, mental fatigue, and dual pressure caused by the integration of formal education and tahfidz programs. This research aims to analyze the dynamics of these psychological challenges and identify the coping strategies used by students to maintain their memorization consistency. The study employed a qualitative approach with a case study method. Data were collected through passive participatory observation, in-depth interviews with students and tahfidz supervisors, and documentation analysis of memorization records. The findings indicate that the main psychological challenges include boredom, emotional exhaustion, concentration difficulties, and pressure to achieve memorization targets. In addition, supportive social interaction, emotional guidance from teachers, adaptive coping strategies, and intrinsic motivation were found to play important roles in strengthening students’ resilience. This study contributes to the development of Islamic educational psychology by emphasizing the importance of integrating mental health support into tahfidz education systems in order to create a more humane and psychologically supportive learning environment.